HybriD-GM: Um Modelo Paralelo para Computação Quântica direcionado às Arquiteturas Híbridas - Avila, Anderson; Moura, Bruno; Bastos, Rafael; Santos, Helida; Lucca, Giancarlo; Cruz, Anderson; Xavier-de-Souza, Samuel; Yamin, Adenauer; Reiser, Renata (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2024: Anais do XXV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2024.244757, 2024)
This paper has as its primary objective to introduce the the HybriD-GM model conception, as well as extend the D-GM environment, providing efficient parallel executions for quantum computing simulations, targeted to hybrid architectures considering both CPU and GPU. By managing projection operators over quantum structures, and exploring coalescing memory access patterns, the HybriD-GM model enables the granularity control, optimizing hardware resources in distributed computations organized as tree data-structures. In the HybriD-GM evaluation, simulations of Shor’s and Grover’s algorithms achieve significant performance improvements in comparison to the D-GM previous version and to the LIQUi|⟩ and ProjectQ simulators.